Arthroscopic treatment of focal osteochondral lesions of the first metatarsophalangeal joint - Kuyucu, Ersin; Mutlu, Harun; Mutlu, Serhat; Gülenç, Barış; Erdil, Mehmet (BioMed Central Ltd., 2017)
Background: Although arthroscopic surgical treatment of the first metatarsophalangeal (MTP) joint involves painful sesamoid excision, synovectomy, debridement, and partial cheilectomy, no gold standard treatment technique has been defined in the literature for hallux rigidus and focal osteochondral lesions. This study aimed to assess the arthroscopic treatment for early-grade focal osteochondral lesions of the first MTP joint and to determine the impact of arthroscopic microhole drill surgery on foot function and activities of daily living in a group of patients who failed conservative treatment. Methods: This prospective study included 14 patients with hallux rigidus and focal osteochondral lesions of the first MTP joint who underwent surgery in 2014 and were followed on a regular basis thereafter. Results: The patients had mean preoperative VPS (visual pain scale) and AOFAS (American Orthopedic Foot and Ankle Society)-Hallux scores of 8.14 ± 0.86 SD and 48.64 ± 4.27, respectively; the corresponding postoperative values of both scores were 1.86 ± 0.66 SD and 87.00 ± 3.70, respectively. Both VPS and AOFAS-Hallux scores changed significantly. Discussion: In this prospective study, we explored the impact of arthroscopic microhole drill surgery on foot function and activities of daily living in patients with focal osteochondral lesions of the first MTP joint. Our results showed significant improvements in VPS and AOFAS scores with this treatment. Conclusions: An arthroscopic microhole drill technique can be used with impressive functional scores and without any complications in patients who failed conservative therapy for hallux rigidus with focal chondral injury.
Keywords: Metatarsophalangeal Joint; Hallux Rigidus; Arthroscopy